Technical abilities of elite wheelchair basketball players - Zacharakis, E.; Apostolidis, N.; Kostopoulos, N.; Bolatoglou, T. (The Sport Journal, 2012)
Wheelchair basketball met a rapid growth in recent decades and became one of the most popular and spectacular sports for people with disabilities. Researchers` efforts to perform tests evaluating the physiological and technical characteristics of the disable athletes have been based on the adoption of tests, used for healthy athletes (7, 15). In addition, different types of disabilities obligated the International Wheelchair Basketball Federation to establish classification degree for the athletes, ranging from 1 to 4.5, according to their disability. The purpose of this study was to evaluate the Greek elite basketball players` technical skills and to compare their performance, (a) with their classification degree and (b) with recent literature. Fourteen (N=14) Greek wheelchair basketball players, all members of the national team, volunteered to perform six skill tests: (a) 20m sprint, (b) free throws, (c) lay-ups, (d) obstacle dribble, (e) pass for accuracy, and (f) pass for distance. The high classification degree athletes, demonstrated significantly higher performance than those with low classification, only in obstacle dribble test (p <.01), but the trend indicated that athletes with high classification degree demonstrated better performance on tests requiring physical abilities (sprint, lay-ups, obstacle dribble, pass for distance), while those with low classification degree performed better on tests requiring skills and concentration (free throws, pass for accuracy). These results are in accordance with recent literature, although Greek basketball players, demonstrated lower performance compared with those of other countries, where wheelchair basketball is widespread . The difference between high and low classification players in obstacle dribble test, caused to the lack of abdominal muscles, while overall performance is affected by the frequency of training and years of involvement with the sport, before the time point of injury.